Hepatitis B Virus Genotype G: The Odd Cousin of the Family - Araujo, Natalia M.; Osiowy, Carla (Frontiers in Microbiology, 2022)
With a widespread distribution but low prevalence worldwide, the hepatitis B virus (HBV) genotype G (HBV/G) is a recently described genotype for which the origin and biology are poorly understood. Some unique features make HBV/G the most peculiar of all genotypes. In this review, we reflect on the major milestones in HBV/G research, highlighting the main aspects of its discovery, molecular epidemiology, and virological and clinical characteristics. We also illustrate common pitfalls in the routine detection, which may lead to underestimated rates of HBV/G infection. Large scale analysis of data from dozens of articles was further performed, with the aim of gaining comprehensive insights into the epidemiological aspects of HBV/G. Finally, we point out recent findings on HBV/G origins and discuss new perspectives regarding the evolutionary history of HBV/G and the plausibility of an African geographic re-emergence of this genotype.